Relationship Between Knowledge And Attitudes Of Housewives With Open Defecation Behavior (BABS) Rw 05 Ciseureuh Village - Hanna Meridian Ocolly; Tri Ardayani; Fahmi Fuadah (CV Media Inti Teknologi, 2025)
Civilian’s access towards a clean and healthy lavatory is a part of basic human sanitary needs. This however is still a big problem in Indonesia. Sewage control plays a big part in a healthy environment. Therefore, sewage mismanagement can lead to environmental damage in the water and soil surrounding the polluted area. This can lead to unexpected disease outbreaks that also affect the resident’s activities. Open defecation are still seen in most traditional based homes including in RW 05 Kelurahan Ciseureuh, Bandung. The purpose of this research’s purpose is to analyze the connection between the knowledge and the action taken towards open defecation Methods. The research approach used is the analytical survey with cross sectional planning. RW 05 Kelurahan Ciseureuh has 230 housewives in tota as population. The data has collected through a questionnaire using frequency distribution and Spearman Rank statistical testing. The results of shows a connection between acknowledging and behaving towards open defecation resulting in p-value 0.028 and the connection between taking action and behaving towards open defecation resulting in p-value 0.049. Conclusion there is a relationship between the knowledge and attitudes of housewives with open defecation (BABS) behavior. RW 05 Cadre is able to work together with M. Ramdan Health Center to provide more education about Open Defecation Behavior (BABS) in order to build awareness of every citizen.